Biobanks for life sciences and personalized medicine: importance of standardization, biosafety, biosecurity, and data management. (October 2020) - Müller, Heimo; Dagher, Georges; Loibner, Martina; Stumptner, Cornelia; Kungl, Penelope; Zatloukal, Kurt
Graphical abstract: Abstract: Biological samples such as tissues, blood and other body fluids, plants or seeds, prokaryotic and eukaryotic cells or isolated biomolecules as well as associated data are the essential raw material for research and development in medicine, biotechnology and agriculture. The collection, processing, preservation, and storage of these resources, in addition to provision of access, are key activities of biobanks or biological resource centres. Biobanks have to ensure proper quality of samples and data, ethical and legal compliance as well as transparent and efficient access procedures. In this context the review places special emphasis on pre-analytical procedures and international standards, which are essential to improving analytical data reliability and reproducibility, as well as on the increasing importance of data management. These requirements of biobanks are demonstrated using the example of pathogen-containing and microbiome biobanks, and refer to needs in cancer research and development.